Performance of three oil palm varieties on the East Coast of North Sumatra. Issue 1 (1st January 2023) - Pradiko, I; Hariyadi,; June, T; Sujadi,
Abstract: The planting material, environmental conditions, and agricultural practices determine the oil palm performance. This research aimed to observe the performance of three oil palm varieties produced by IOPRI in Adolina Estate, Serdang Bedagai, North Sumatra. Adolina Estate is located on the eastern part and has a distinctive equatorial rainfall type with a sandy clay loam soil texture. The DyP Dumpy, DxP PPKS 540, and DxP Langkat varieties have been planted since 2010 in the same block with similar soil conditions and agricultural practices with total samples of 101, 147, and 124 trees, respectively. The growth parameters were height, length of rachis, petiole cross-section (PCS), and leaf area (LA), while the production parameters observed included the average bunch number, bunch weight, and yield. The results showed that DyP Dumpy had the slowest height growth with the most extended rachis length. DxP PPKS 540 has the highest average of PCS and LA, while the DxP Langkat had the fastest height growth and shortest rachis length. Furthermore, the DxP PPKS 540 variety produced the highest average yield, 24.85 tons ha −1, while DyP Dumpy and DxP Langkat have 23.19 tons ha −1 and 23.95 tons ha −1, respectively.